Gratitude mediated by positive thinking: Does it influence resilience among people with non-congenital disabilities? - Frengki Seran; Widyana, Rahma (Insight: Jurnal Ilmiah Psikologi, 2024)
People with non-congenital physical disabilities experience many psychological challenges, including the emergence of negative thoughts. The study aims to identify the relationship between gratitude and resilience as mediated by positive thinking in non-congenital disabled people. The research subjects were 34 people with non-congenital disabilities, men and women, aged 21 - 55 years old. Data collection used three scales developed by the researchers, namely the Gratitude scale, Positive Thinking scale, and Resilience scale. Data was analyzed using simple regression, the causal step method developed by Baron & Kenny (1986), and the Sobel test. The analysis results showed that (1) there was a positive relationship between gratitude and resilience in non-congenital disabled people, indicating that the higher the gratitude, the higher the resilience. (2) There was a positive relationship between positive thinking and resilience in a non-congenital disabled person, indicating that the greater the positive thinking, the greater the resilience. (3) There was a positive relationship between gratitude and positive thinking in non-congenital disabled people, indicating that the greater the gratitude, the greater the positive thinking, and conversely the lower the gratitude, the lower the positive thinking. (4) There was a positive relationship between gratitude and resilience, mediated by positive thinking in non-congenital disabled people. Positive thinking entirely functions as a mediator and has a significant indirect relationship between gratitude and resilience, where gratitude influences positive thinking first, then positive thinking influences resilience in this study’s samples of non-congenital disabled people. Keyword: Positive thinking; gratitude; resilience; non-congenital disabilities.